Multilevel Selection and the Theory of Evolution Historical and Conceptual Issues (Springer International Publishing, 2018)
This book puts multilevel selection theory into a much needed historical perspective. This is achieved by discussing multilevel selection in the first half of the twentieth century, the reasons for the energetic rejection of Wynne-Edwards' group selectionist stance in the 1960s, Elisabeth Lloyd's contribution to the units of selection debate, Price's hierarchical equation and its possible interpretations and, finally, species selection in macroevolutionary contexts. Another idea also seems to emerge from these studies; namely, that perhaps a more sure-footed position for multilevel selection theory would be acquired if we were to show a renewed interest in 'old group selection', i.e. in scenarios in which the differential reproduction of the groups themselves affects the frequencies of either individual-level or group-level traits. This book will be of interest to philosophers and historians of biology, as well as to theoretically inclined biologists who have an interest in multilevel selection theory.